Improvement of business decision-making in IT industry using the MCDM approach - Stanujkic, Maja; Popovic, Gabrijela; Vukotic, Svetlana; Karabasevic, Darjan; Stanujkic, Dragisa (Industrija, 2024)
The selection of suitable individuals for key roles within the organization can significantly affect the business efficiency and performance of the organization. For this reason, this article discusses a multi-criteria decision-making procedure for candidates’ evaluation in the Information Technologies industry (IT) based on the combined use of Simplified Pivot Pairwise Relative Criteria Importance Assessment (PIPRECIA-S) and Weighted Sum with Preferred Levels of Performances (WS-PLP) methods. In the proposed approach, PIPRECIA-S was used to determine the criteria weights, while the WS-PLP method was used to evaluate candidates and harmonize the views of decision-makers attitudes. The applicability and usability of the proposed approach were considered in the case of selecting an IT Project Manager in an IT company, but it can easily be adapted for similar cases of candidate selection.